In vitro models for peripheral nerve regeneration. (28th September 2015) - Geuna, S.; Raimondo, S.; Fregnan, F.; Haastert‐Talini, K.; Grothe, C.
Abstract: The study of peripheral nerve repair and regeneration is particularly relevant in the light of the high clinical incidence of nerve lesions. However, the clinical outcome after nerve lesions is often far from satisfactory and the functional recovery is almost never complete. Therefore, a number of therapeutic approaches are being investigated, ranging from local delivery of trophic factors and other molecules to bioactive biomaterials and complex nerve prostheses. Translation of the new therapeutic approaches to the patient always requires a final pre‐clinical step using in vivo animal models. The need to limit as much as possible animal use in biomedical research, however, makes the preliminary use of in vitro models mandatory from an ethical point of view. In this article, the different types of in vitro models available today for the study of peripheral nerve regeneration have been ranked by adopting a three‐step stair model based on their increasing ethical impact: (i) cell line‐based models, which raise no ethical concern; (ii) primary cell‐based models, which have low ethical impact as animal use, although necessary, is limited; and (iii) organotypic ex vivo ‐based models, which raise moderate ethical concerns as the use of laboratory animals is required although with much lower impact on animal wellbeing in comparison to in vivo models of peripheral nerve regeneration. This article aims to help researchers in selecting the best experimental approach for their scientific goals driven by the 'Three Rs' (3Rs) rules (Replacement, Reduction or Refinement of animal use in research) for scientific research. Abstract : This review describes in vitro models suitable to reduce the use of animals in peripheral nerve regeneration research and rank these models according to the ethical concerns, costs and technical efforts they raise and their similarity to complex in vivo models needed for the final step for translation of new developments into the clinic.